Historical reconstruction of Sennacherib's campaign against Judah and Jerusalem in 701 B.C. - Matty, N (2014)
This thesis has attempted a reconstruction of Sennacherib’s campaign against Judah in 701. The purpose of this resconstruction has not been to reach a definitive picture of the events of 701 but rather to come to the best possible hypothesis based upon a wide study of the relevant texts. The best historical hypothesis concerning what happened in 701 must attempt to give equal weight to each piece of evidence in each relevant area, whether literary or archaeological. My justification for returning to this much-discussed area therefore is that previous scholarship has failed to meet this criterion for giving the best historical hypothesis. Over the course of my investigation I examined the relevant Assyrian inscriptions, not merely those relating to the third campaign, and the purported instances of biblical evidence, as well as engaging with archaeological and literary considerations. I showed that the most important theories offered up to this point each contradict or contend with an important piece of contrary evidence. Then, I suggested a view of my own which is, as far as possible, commensurate with all the evidence available.